NPK fertilization effects on concentration of nutrients in Valência orange leaves - Basso, Clori; Mielniczuk, João; Bohnen, Humberto (Pesquisa Agropecuaria Brasileira, 2014)
In a field experiment of Valencia orange (Citrus sinensis Osbeck) growing in a sandy acid soil, with 4 N, 3 P and 4 K fertilizer levels, the effects of NPK fertilization on the nutrient concentration in the leaves was evaluated. N and Cu contents in the leaves were high, while P and Zn levels were low, in all treatments. Increasing the levels of N, P2O5 and K2O fertilization resulted in an increase of the N, P and K concentration in the leaves, respectively. Crescent levels of N fertilization raised Mn and decreased Ca concentration in the leaves. P and K contents in the leaves correlated positively. With a great availability and absorption of K, reduction on the foliar contents of Mg and Ca occurred.